Effect of different types of solvent on extraction of phenolic compounds from cosmos caudatus - Nur Ain, Sukri (2012)
The preliminary screening indicated that Cosmos caudatus had extremely high antioxidant capacity. The antioxidant activity of most of the plant produced is mainly due to the presence of phenolic compounds. Among the phytochemicals, phenolic compounds are the main contributor of antioxidant activity in plant extracts due to their higher value in total phenolic content.The purpose of this study is to investigate the effect of different types of solvent with 50%,70% and 100% concentration of each solvent on extraction of phenolic compounds from Cosmos caudatus.The soxhlet extractor was used in this study.Total phenols in the extract was determine using Folin-Ciocalteu (FC) assay. From the results,100% ethanolic extract showed the highest of total phenolic content with 15.61 mgGAE/g. However the antioxidant activity was only 14.15%. Meanwhile,70% acetone extract exhibited the highest inhibition of DPPH.The value obtained was 7.77 mgAAE/g with the antioxidant activity of 84.78%. The polarity of the solvent affects the efficiency of the extraction,total phenolic content and antioxidant activity of the obtained extracts.Total phenolic content is not the only contributor to its antioxidant activity.The existence of other components in fresh extract such as enzymes and vitamin may directly react with free radicals in addition to polyphenolic compound.Further research is warranted to explore the individual or major polyphenolic groups and other bioactive compounds in the Cosmos caudatus.